Communication and Library Marketing. Literature Review, academic and professional courses in Italy - Pier Francesco Miccichè (JLIS.it)
This paper sets out to sketch a review of the literature, training courses and scientific and professional debate on library marketing and promotion, with a particular focus on the Italian case. Starting from Norman O. Gene's detailed account (1982) of the emergence of library marketing in international literature, the first section describes its origin and development in Italy, tracing the timeline of the main articles and monographs on the topic. In the second section, focus shifts to conferences and seminars, which often resulted in editorial outputs. The third paragraph addresses the librarians' training in communication and library marketing in Italy, both in the form of university classes and workshops for professionals, finding them insufficient for the today’s scenario. Finally, blogs, newsletters and podcasts on library marketing in Italy and abroad as well as international awards for library marketers are discussed. In all cases, the Italian scenario is considered through comparison with the international one. The topic is clearly intertwined with the marketing’s evolution as a discipline not exclusively devoted to profit, and its transition from analogical methods of promotion to the contemporary digital ones provided by ICT and social media. The study highlights the need for further research and commitment on digital marketing for cultural institutions in Italy.